Beyond Objective and Subjective: Assessing the Legitimacy of Religious Claims to Accommodation - Weinstock, Daniel (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2011)
There are at present two ways in which to evaluate religiously-based claims to accommodation in the legal context. The first, objective approach holds that these claims should be grounded in « facts of the matter » about the religions in question. The second, subjective approach, is grounded in an appreciation by the courts of the sincerity of the claimant. The first approach has the advantage of accounting for the difference between two constitutional principles : freedom of conscience on the one hand, and freedom of religion on the other. It has the disadvantage of transforming courts into expert bodies on religious matters. The subjective approach has a harder time accounting for the distinction. It also risks giving rise to a proliferation of claims. A plausible synthesis between the two approaches requires that we uncover the normative grounds justifying the granting by liberal democracies of religious accommodation. An analogous argument to that put forward by Kymlicka in the case of minority nations identifies the interest that citizens have in being able to exercise their « cultural agency » : the creative reappropriation and reinterpretation of the rituals, practices and norms of religious traditions.